Identifying the Dimensions, Components, and Indicators of an Organizational Learning Model Based on Multiple Intelligences in Iranian Schools - Ghahri, Aref; Kargar Shahamat, Bahman; Roohi Issa Lou , Mohammad (Assessment and Practice in Educational Sciences, 2026)
The objective of this study was to identify the dimensions, components, and indicators of an organizational learning model based on multiple intelligences in Iranian schools. This research employed a sequential exploratory mixed-methods design consisting of qualitative and quantitative phases. In the qualitative phase, a meta-synthesis of prior studies and semi-structured interviews with educational experts, teachers, and school administrators were conducted to extract organizing and basic themes using thematic analysis with open and axial coding. Data sources included interview transcripts, written reflections, observational notes, and theoretical literature. In the quantitative phase, a questionnaire was developed based on the qualitative findings and administered to a broader sample of school teachers and administrators. The psychometric properties of the scale were evaluated, and structural equation modeling (SEM) was used to examine the relationships among the identified components and validate the proposed model of organizational learning based on multiple intelligences. Inferential analyses demonstrated that the proposed organizational learning model exhibited strong validity and reliable fit indices within SEM. All three global constructs—empowering learning environment, capacity building for sustainable organizational learning, and educational leadership based on multiple intelligences—significantly predicted organizational learning outcomes. Path coefficients indicated that leadership based on multiple intelligences had the strongest direct effect on organizational learning, followed by capacity-building mechanisms and learning environment variables. Subscale analyses confirmed that components such as psychological safety, experiential learning, use of feedback and data, and intelligence-based leadership competencies significantly contributed to the predictive power of the model. The study concludes that organizational learning in schools is strengthened when environments support collaboration, reflective practice, psychological safety, and technology-enhanced instruction, and when leaders integrate multiple intelligences into communication, decision-making, and instructional guidance. The validated model provides a comprehensive framework for improving learning culture, professional development, and organizational effectiveness in Iranian schools.